Performativity and creativity in senior secondary drama classrooms. Issue 1 (2nd January 2016) - Lambert, Kirsten; Wright, Peter R.; Currie, Jan; Pascoe, Robin
Abstract: This article examines the intersection between the senior secondary drama classroom, creativity and neoliberalism. Informed by a research project involving fifteen West Australian drama teachers and thirteen students, it considers the drama classroom as one site where tensions between the performative needs of neoliberal education and the more humanistic desires that drama teachers embody are enacted. This paper suggests that drama education can be a powerfully transformative vehicle for creative and innovative thinking because of its spatially unique classroom environment and embodied nature. However, collisions between rhetoric and reality, social good and economic return, can mean that young people are denied opportunities for choice and the capability development that drama education brings.